The 35-kDa mammalian splicing factor SC35 mediates specific interactions between U1 and U2 small nuclear ribonucleoprotein particles at the 3' splice site. - Fu, X D (1992)
The splicing factor SC35 is required for the first step of the splicing reaction and for the assembly of the earliest ATP-dependent complex detected by native gel electrophoresis (A complex). Here we investigate the role of SC35 in mediating specific interactions between U1 and U2 small nuclear ribonucleoprotein particles (snRNPs) and the 5' and 3' splice sites of pre-mRNA. We show that U1 snRNP interacts specifically with both the 5' and 3' splice sites in the presence of ATP and that SC35 is required for these ATP-dependent interactions. Significantly, the SC35-dependent interaction between U1 snRNP and the 3' splice site requires U2 snRNP but not the 5' splice site. We also show that SC35 is required for the ATP-dependent interaction between U2 snRNP and the branch-point sequence. We conclude that SC35 may play an important role in mediating specific interactions between splicing components bound to the 5' and 3' splice sites.